The Effect of Circular Economy Practices on Financial Performance of Creative MSMEs in Surakarta - Rizal, Moch. Deni; Prihatiningsih, Margaretha (LifeSciFi, 2026)
Rising raw material costs and global sustainability demands compel MSMEs to shift from linear to circular economic models. However, the economic impact of this transition on small businesses remains debated. This study aims to investigate the effect of circular economy practices on the perceived financial performance of creative MSMEs in Surakarta. This research offers novelty by challenging the stigma that sustainability practices are merely cost burdens, highlighting their potential for efficiency instead. Employing a quantitative explanatory approach, data were collected through a survey of 73 MSME practitioners and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that circular economy practices have a positive and significant effect on perceived financial performance at the 10% level, with a dominant path coefficient of 0.656. Empirically, the adoption of reduce, reuse, and recycle principles proves to be a resource efficiency mechanism capable of enhancing profitability. This study recommends that MSME owners integrate waste management and material efficiency as core business strategies for long-term business sustainability.